Halal Tourism : Sikap Toleransi Wisatawan Lokal Terhadap Isu Arabisasi Wisata Syariah Pulau Santen di Banyuwangi - Latifah, Siti Nur (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Banyuwangi is one of the provinces in Indonesia which is located at the easternmost tip of the island of Java which is developing the concept of sharia tourism, specifically on Santen Island. However, in the process of developing this destination, several parties consider the concept of sharia tourism to be a cult of certain religions and groups. The aim of this research is to determine the tolerance attitude of tourists regarding the issue of Arabization that is circulating amidst the development of halal tourism. The research approach used is quantitative with a survey method using a modified Likert scale. The research results show that respondents are quite tolerant of tourism development because it is quite in accordance with the sharia tourism concept which includes cleanliness, safety and comfort in worship. The concept of sharia is more about the comfort of traveling, not a particular religious doctrine